Efeito da desnutrição perinatal sobre o comportamento alimentar e função termogênica em ratos adultos - Miranda, Ginislene Dias Souza (2020)
Early nutritional imbalances are associated with metabolic diseases development in adulthood. It seems to be closely related to neuroendocrine modulations due to nutritional scarcity and/or hormonal changes. In the present study, we aimed to evaluate the effect of maternal calorie restriction during the first 2/3 of breastfeeding on the adult rat-offspring’s feeding behavior, biometrical, biochemical and thermogenesis parameters. Wistar rats underwent dietary restriction (50%) during the initial 2/3 of lactation (FR50 group) the control rats (Cont group) were fed ad libitum throughout lactation. At birth, litter size was adjusted to 8 pups. Ratoffspring milk ingestion was evaluated at 6th, 11th and 16th ages. At 12th day of lactation, milk was collected to creamatocrit and biochemical assessment and at 22-days-old rat-offspring were weaned. Body weight and food and water intake were evaluated every two days. At 40-daysold, the feeding preference was evaluated through the simultaneous offer of standard chow (normal fat-diet, NFD) and hypercaloric diet (high fat-diet, HFD) by 10 days, and at 90-daysold, individual food intake in dark cycle was assessed. At 100-days-old, rat-offspring were euthanized to collect blood sample and white and brown adipose tissue (BAT), as well as skeletal muscle to biochemical, biometrical and molecular assessment. Compared to milk from Cont group, in FR50’s milk was found increased values of glucose (72.52%, P<0.01), total cholesterol (79.80%, P<0.05), triglycerides (30.10%, P<0.05), total protein (53.17%, P<0.05) and energy content (29.35%, P<0.01). Regarding rat-offspring, FR50 rats displayed lean phenotype (17.82%, P<0.001) associated to high BAT mass (P<0.05), hyperphagia (12.59%, P<0.01) and preference for HFD ingestion (+68.27%, P<0.01). In relation to Cont group, FR50 rats increased the values of total-cholesterol (33.12%, P<0.001), triglycerides (26.88%, P<0.05), LDL-cholesterol (52.96%, P<0.001), VLDL-cholesterol (35.90%, P<0.01), and reduced by 8.51% the HDL-cholesterol values (P<0.05). In addition, RA50 rats showed an increase in Castelli indexes (P <0.001).While the protein expression of β3-AR was reduced by 40% (P<0.05), the expression of UCP1 was increased by 46.28% (P<0.05) in BAT. In conclusion, even though adult FR50 rats remain phenotypically lean, displayed hyperphagia and HFD preference as well as atherogenic high risk that is suggestive to consequent development of dyslipidemia-associated vascular diseases and high thermogenesis capacity in the BAT.